Role of seed infection for the near and far distance dissemination of wheat blast caused by Magnaporthe oryzae pathotype Triticum - Surovy, Musrat Zahan; Islam, Tofazzal; von Tiedemann, Andreas (Frontiers in Microbiology, 2023)
Magnaporthe oryzae pathotype Triticum (MoT) is a devastating fungal phytopathogen causing wheat blast disease which threatens wheat production in warmer climate zones. Effective disease control is hampered by the limited knowledge on the life cycle, epidemiology, and pathogenicity of MoT. Since MoT mainly infects and colonizes the inflorescences of wheat, infection, invasion routes and colonization of MoT on wheat ears and in wheat seeds were investigated in order to assess potential seed transmission mechanisms. MoT was spray inoculated on two wheat cultivars (Sumai 3, susceptible and Milan, resistant) at three spike maturity stages (full ear emergence, growth stage (GS) 59; mid flowering, GS 65; and end of flowering, GS 69). Incidence of MoT on Sumai 3 seeds was 100% and in Milan 20-25%. MoT sporulation rate on Sumai 3 contaminated seeds was more than 15 times higher than on Milan. The localization of MoT within various seed tissues was followed by light and confocal laser scanning microscopy (CLSM). Invasion of MoT in seeds predominantly occurred in the caryopsis germ region, but entry via other seed parts was also observed, confirming the potential of intense colonization of MoT in wheat grains. Fungal spread in wheat plants growing from MoT infected seeds was monitored through plating, microscopic and molecular techniques. Under greenhouse conditions, no spread of MoT from infected seeds to seedlings later than GS 21 or to ears was detected, neither in Milan nor in Sumai 3. We therefore conclude, that MoT may not systemically contaminate inflorescences and seeds in both susceptible and resistant wheat cultivars. However, initial blast symptoms, only found on seedlings of Sumai 3 but not Milan, resulted in the formation of new conidia, which may serve as inoculum source for plant-to-plant dissemination and airborne ear infection in the field (short distance spread). Ultimately, the inoculum may infect young inflorescences in the field and contaminated seeds. Our findings again stress the risk of long-distance dissemination of wheat blast across continents through MoT-contaminated seeds. This underlines the importance of mandatory use of healthy seeds in strategies to control further spread of wheat blast.